UNDERSTANDING NATURAL REGENERATION IN BURNED TROPICAL PEATLAND: A STRATEGY TO ACCELERATE THE FOREST RECOVERY PROCESS - Dwi Puji Lestari; Taryono Darusman; Fransiskus Harsanto; Desra Arriyadi; Ginanjar Ginanjar (BIOTROPIA, 2021)
The 2015 massive forest fires across Central Icalimantan left large areas of burned peatlands that need to be restored, demanding substantial resources. To understand natural regeneration of burned peatland and how planting might accelerate its recovery process, the regrowth of burned peatlands was measured with different fire frequencies. Three transects were established. Each transect consisted of five 20 x 20 m plots with 30 m intervals. All woody species were recorded and classified into three categories as new regrowth, regrowth, and remnant trees that survive from the last fire. In addition, data from fifteen 2 x 2 m permanent natural regeneration plots and evaluation on survival rate of 2017 planting were also analyzed. Research results suggested that the absence of remnant trees due to frequent or severe fires does not always impede the emergence of new recruitments, although diversity of forest regrowth is likely to be affected by its proximity to forest remnants. The floristic composition also showed a domination of pioneer species, giving evidence that forest recovery is initiated. Our study indicated that the combination of fire frequency, fire intensity, and proximity to remnant forest will produce different degrees of forest recovery, and the result will be unique for each site. It is concluded that to support the recovery process through planting activity, the successional stage of the designated sites should be determined first. The common planting method on large areas with mixed climax-high valuable trees was not beneficial unless the restoration sites had reached the later stages of succession.